2023
DOI: 10.1002/adma.202301005
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Robust Amphibious Soft Robot with Imperceptibility Based on a Water‐Stable and Self‐Healing Ionic Conductor

Abstract: Dielectric elastomer actuators (DEAs) are widely exploited for actuating soft machines and granting soft robots with capability to operate in both underwater and on‐land environments is important to make them adapt to more complex situations. Here, a DEA‐driven, highly robust, amphibious imperceptible soft robot (AISR) based on an all‐environment stable ionic conductive material is presented. A soft, self‐healable, all‐environment stable ionic conductor is developed by introducing cooperative ion–dipole intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Interestingly, even under such harsh operating conditions, our CPS exhibits outstanding durability at 150 compression–release cycles (Figure S17). Due to the concerns about the potential penetration of the ionic liquid used in the electrode gel into the dielectric material and to ensure the long-term stability of the dielectric layer, we employed a characterization method following recent literature . We compared the FTIR spectra of the pristine MFE with those of the MFE disassembled from the CPS device, which was suspected to have potential ionic liquid infiltration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, even under such harsh operating conditions, our CPS exhibits outstanding durability at 150 compression–release cycles (Figure S17). Due to the concerns about the potential penetration of the ionic liquid used in the electrode gel into the dielectric material and to ensure the long-term stability of the dielectric layer, we employed a characterization method following recent literature . We compared the FTIR spectra of the pristine MFE with those of the MFE disassembled from the CPS device, which was suspected to have potential ionic liquid infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the concerns about the potential penetration of the ionic liquid used in the electrode gel into the dielectric material and to ensure the long-term stability of the dielectric layer, we employed a characterization method following recent literature. 48 We compared the FTIR spectra of the pristine MFE with those of the MFE disassembled from the CPS device, which was suspected to have potential ionic liquid infiltration. However, upon examining the results, the two curves were found to be very similar (Figure S18).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The interaction of dipoles at the interface plays a crucial role in various fields such as perovskite, 17 lithium-ion batteries, 18 and polymer materials. 19 In molecular junctions, dipoles affect the efficiency of tunneling transport or the work function of electrodes. Douglas Natelson et al observed a linear vibrational Stark effect due to the permanent electric dipole moment.…”
Section: Introductionmentioning
confidence: 99%
“…8 Unique features of these organisms have inspired people to construct a large number of surfaces that imitate special functions, which have been applied for encryption, 9−11 substrates delivering, 12−14 and self-healing device. 15,16 Currently, many studies in this area are aimed at controlling water via liquid capillary force (F L ). 17−19 Because of surface energy differences, water tends to move from hydrophobic to hydrophilic areas.…”
mentioning
confidence: 99%
“…Liquid manipulation is an integral part of the ecosphere. Many organisms rely on it for survival, such as beetles in the desert, pitcher plants, and cacti . Unique features of these organisms have inspired people to construct a large number of surfaces that imitate special functions, which have been applied for encryption, substrates delivering, and self-healing device. , Currently, many studies in this area are aimed at controlling water via liquid capillary force ( F L ). Because of surface energy differences, water tends to move from hydrophobic to hydrophilic areas. , Surface wettability gradients are key features for the success of the process, , and therefore, controllable fabrication of surfaces with tailored wettability is crucial. …”
mentioning
confidence: 99%